2016
DOI: 10.1080/13540602.2016.1211102
|View full text |Cite
|
Sign up to set email alerts
|

Validating a model of effective teaching behaviour of pre-service teachers

Abstract: Although effective teaching behaviour is central for pupil outcomes, the extent to which pre-service teachers behave effectively in the classroom and how their behaviour relates to pupils' engagement remain unanswered. The present study aims to validate a theoretical model linking effective pre-service teaching behaviour and pupil's engagement, incorporating the role of context and teacher characteristics. The study included a sample of 264 pre-service teachers from 64 secondary schools throughout the Netherla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 52 publications
5
37
1
7
Order By: Relevance
“…However, our study revealed that differentiation and teaching learning strategies were perceived less positively in Netherlands. This finding is consistent with past studies indicating that Dutch teachers are still struggling with the implementation of these two teaching domains in their daily classroom practices (Maulana et al, 2017).…”
Section: Differences In Perceived Teaching Behavior Across Countriessupporting
confidence: 93%
See 1 more Smart Citation
“…However, our study revealed that differentiation and teaching learning strategies were perceived less positively in Netherlands. This finding is consistent with past studies indicating that Dutch teachers are still struggling with the implementation of these two teaching domains in their daily classroom practices (Maulana et al, 2017).…”
Section: Differences In Perceived Teaching Behavior Across Countriessupporting
confidence: 93%
“…This framework has been integrated in teacher education as well as in in-service teacher professional development across the country (van Tartwijk et al, 2014). In addition, the integration of teaching effectiveness frameworks into some Dutch teacher education programs and teacher professional development has also been done, putting a strong importance of learning climates as a pre-requisite for more effective teaching behavior (Maulana et al, 2017). On the other hand, the relatively low rating of Indonesian teachers on learning climate may also be associated with the still commonly applied student-centered teaching approach (de Ree, 2016;Fasih et al, 2018).…”
Section: Differences In Perceived Teaching Behavior Across Countriesmentioning
confidence: 99%
“…Finally, it will be worth investigating how teachers can be equipped for using the feedback they receive on student progress for differentiating their teaching. It is generally known that differentiating instruction in line with differences between students is a very complex task for which teachers are only trained to a limited extent during their pre-service and in-service training (Maulana, Helms-Lorenz, & Van de Grift, 2016). We need to investigate what effective teaching with DFATs entails and how the skills needed for such forms of teaching can be trained effectively.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated by the example above, the question of how to enhance students' motivation is still a major challenge for secondary school teachers worldwide (OECD, 2015). For example, Maulana et al (2017) indicated that motivating students is one of the most complex competences for teachers: in the Netherlands, less than 60% of the teachers succeed in involving students in the classroom by using activating instruction. In line with these findings, the OECD (2015) report indicated that many Dutch students are not motivated.…”
Section: Introductionmentioning
confidence: 99%